Hope As The Provision For Psychological Security Of The Person And The Society - Labunskaya, Vera (Զանգակ հրատ.)
The article discusses various approaches to understanding the function of hope in human life. The author attempts to analyze the functional orientation of hope based on its types. The rationale for the study of hope as a multidimensional formation in the context of human life and person's attitude to life is presented. The paper analyzes the conception of hope among Russians, discusses the relationship between different types of hope and valence (positive-negative) of evaluations of different stages of one's life course. It is emphasized that high level of hopelessness combined with negative attitude towards life reduces the psychological security of a person.
Keywords: Psychology